Isoflavonoid-Rich Flemingia macrophylla Extract Attenuates UVB-Induced Skin Damage by Scavenging Reactive Oxygen Species and Inhibiting MAP Kinase and MMP Expression - Chiang, Hsiu-Mei (Hindawi Publishing Corporation, 2013)
In this study, we investigated the antioxidant activity and anti-photoaging properties of an extract of Flemingia macrophylla, a plant rich in isoflavonoid content. Pretreatment of fibroblasts with Flemingia macrophylla extract (FME) inhibited elastase activity, promoted the protein expression of type I procollagen, and attenuated the phosphorylation of mitogen-activated protein (MAP) kinase and the protein expression of matrix-metalloproteinase- (MMP-) 1, 3, and 9. The IC(50) values were 2.1 μg/mL for DPPH radical scavenging ability, 366.8 μg/mL for superoxide anion scavenging ability, 178.9 μg/mL for hydrogen peroxide scavenging ability, and 230.9 μg/mL for hydroxyl radical scavenging ability. Also, exposure of erythrocytes to various concentrations of FME (50–500 μg/mL) resulted in a dose- and time-dependent inhibition of AAPH-induced hemolysis. In human fibroblasts, FME at 10 μg/mL was shown to be a potent scavenger of UV-induced reactive oxygen species (ROS). The antioxidant and anti-photoaging properties of FME make it an ideal anti-intrinsic aging and anti-photoaging agent.